Factors associated with enrollment into a clinical trial of caregiver-implemented intervention for infants at risk for autism spectrum disorder. (October 2020) - Bradshaw, Jessica; Trumbull, Ashley; Stapel-Wax, Jennifer; Gillespie, Scott; George, Nisha; Saulnier, Celine; Klaiman, Cheryl; Woods, Juliann; Call, Nathan; Klin, Ami; Wetherby, Amy
Early intervention has been established as efficacious in addressing developmental delays in young children with autism spectrum disorder. Evidence that caregiver-implemented interventions are feasible and effective for young children with autism spectrum disorder is emerging, yet research suggests there are barriers to enrollment in clinical trials of these interventions for infants at risk for autism. This study identifies factors associated with enrollment in a clinical trial of a caregiver-implemented intervention for 12-month-old infants at risk for autism spectrum disorder. As part of a large longitudinal study, fifty-seven infants were deemed eligible for intervention based on several converging indicators of autism risk. Of these eligible infants, 44% declined enrollment in the intervention study. Examination of factors associated with families who declined enrollment compared to those who agreed to enroll revealed maternal full-time work status, household income, and distance to the clinic as significant predictors. In contrast, autism red flags and parental concern were not significantly associated with enrollment. These results highlight the need for more research on how parental understanding of, and willingness to act on, early social-communication delays impacts intervention study enrollment. Future research can then examine how to address these barriers to enrollment in caregiver-implemented intervention studies. Lay abstract: Early intervention helps to address developmental delays in young children with autism spectrum disorder. Yet, research suggests there are barriers to enrollment into research studies that test the effectiveness of these interventions for infants at risk. This study identifies family characteristics that were associated with agreement to enroll in a clinical trial of early intervention for 12-month-old infants at risk for autism spectrum disorder. As part of a large longitudinal study, infants were evaluated for early signs of autism spectrum disorder at 1 year of age. Of the fifty-seven infants who were showing signs of autism and deemed eligible for the early intervention trial, 44% declined enrollment. Results suggest that families were more likely to decline enrolling into the intervention study if the mother was working full time, the total household income was between US$60, 000 and US$100, 000, and they lived further from the clinic. In contrast, infant autism symptoms and parental concern at 12 months were not significantly associated with enrollment. These findings highlight the need for intervention studies that are more accessible to parents, for example, intervention that takes place in the home, in addition to more research on how parental understanding of, and willingness to act on, early social-communication delays impact intervention study enrollment. Future research can then examine how to address these barriers to enrollment in early intervention studies. Such findings will shed light on best practices for dissemination of early identification and intervention strategies.